Pre-procedural fasting for coronary interventions: is it time to change practice?. Issue 8 (12th February 2014) - Hamid, Tahir; Aleem, Qaiser; Lau, Yeecheng; Singh, Ravi; McDonald, John; Macdonald, John E; Sastry, Sanjay; Arya, Sanjay; Bainbridge, Anthony; Mudawi, Telal; Balachandran, Kanarath
Abstract : Introduction: Traditionally, patients are kept nil-per-os/nil-by-mouth (NPO/NBM) prior to invasive cardiac procedures, yet there exists neither evidence nor clear guidance about the benefits of this practice. Objectives: To demonstrate that percutaneous cardiac catheterisation does not require prior fasting. Methods: The data source is a retrospective analysis of data registry of consecutive patients who underwent percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS) and stable angina at two district general hospitals in the UK with no on-site cardiac surgery services. Results: A total of 1916 PCI procedures were performed over a 3-year period. None of the patients were kept NPO/NBM prior to their coronary procedures. The mean age was 67±16 years. 1349 (70%) were men; 38.5% (738/1916) had chronic stable angina, while the rest had ACS. 21% (398/1916) were diabetics while 53% (1017/1916) were hypertensive. PCI was technically successful in 95% (1821/1916) patients. 88.5% (1697/1916) had transradial approach. 77% (570/738) of elective PCI patients were discharged within 6 h postprocedure. No patients required emergency endotracheal intubation and there were no occurrences of intraprocedural or postprocedural aspiration pneumonia. Conclusions: Our observational study demonstrates that patients undergoing PCI do not need to be fasted prior to their procedures.